New Insights into the Potential Inhibitory Effects of Native Plants from Cyprus on Pathogenic Bacteria and Diabetes-Related Enzymes - Christou, Atalanti; Stavrou, Constantina; Michael, Christodoulos; Botsaris, George; Goulas, Vlasios (My University, 2024)
Plants possess endless structural and chemical diversity, which is peerless with any synthetic library of small biomolecules, inspiring novel drug discovery. Plants are widely applied to encounter global health challenges such as antimicrobial resistance and diabetes. The objective of this work was to evaluate the antibacterial and antidiabetic potency of native plants grown in Cyprus. All plants were sequentially extracted with solvents of increasing polarity, namely hexane, acetone, methanol, and water. First, the phenolic and flavonoid contents of the extracts were assessed. Afterwards, the bacteriostatic and bactericidal potency of plant extracts were tested against a panel of six bacteria using the broth microdilution method, whereas the inhibitory effects on alpha-glucosidase and alpha-amylase enzymes were also determined with the employment of microplate assays. The results highlighted the superiority of Sarcopoterium spinosum as a potential enzyme inhibitor, while a knowledge base was also acquired for the inhibitory potential of all plants. Daucus carota, Ferula communis, and Tordylium.aegyptiacum displayed additionally outstanding bacteriostatic and bactericidal effects on Gram-positive bacteria at concentrations of 250 µg mL−1 and 500 µg mL−1. Overall, the present study describes the antibacterial and inhibitory activity against carbohydrate digestive enzymes of native plants grown in Cyprus delivering the first reports for many plant species.
Keywords: antimicrobial activity; extracts; flavonoids; phenolic compounds; alpha-glucosidase; alpha-amylase; Gram-negative bacteria; Gram-positive bacteria